Strong boys and supergirls? School professionals' perceptions of students' mental health and gender in secondary school. Issue 3 (3rd July 2019) - Odenbring, Ylva
ABSTRACT: During the first decades of the twenty-first century, adolescents' perceived stress has been reported to be an important factor in explaining the health problems among students in Swedish schools. Based on interviews with key professionals working in the student welfare team in three secondary schools, the present article aims to contribute new knowledge concerning how the school professionals describe and explain students' mental health with regard to gender and the kind of support the schools offer to vulnerable students. Norms connected to the "supergirl" and respectable girl framed the explanations for girls' health-related problems, whereas the explanations for boys' health-related problems tied to a theme of marginalised masculinities. The findings lead to recommendations concerning the need to recognise and problematise students' mental health, as well as the need for more preventive work on student welfare issues, in schools and in other societal institutions.